Guidance for diagnosing autoimmune pancreatitis with biopsy tissues. Issue 10 (6th August 2020) - Notohara, Kenji; Kamisawa, Terumi; Fukushima, Noriyoshi; Furukawa, Toru; Tajiri, Takuma; Yamaguchi, Hiroshi; Aishima, Shinichi; Fukumura, Yuki; Hirabayashi, Kenichi; Iwasaki, Eisuke; Kanno, Atsushi; Kasashima, Satomi; et al.
Abstract : The biopsy‐based diagnosis of autoimmune pancreatitis (AIP) is difficult but is becoming imperative for pathologists due to the increased amount of endoscopic ultrasound‐guided biopsy tissue. To cope with this challenge, we propose guidance for the biopsy diagnosis of type 1 AIP. This guidance is for pathologists and comprises three main parts. The first part includes basic issues on tissue acquisition, staining, and final diagnosis, and is intended for gastroenterologists as well. The second part is a practical guide for diagnosing type 1 AIP based on the AIP clinical diagnostic criteria 2018. Inconsistent histological findings, tips for evaluating IgG4 immunostaining and key histological features including the ductal lesion and others are explained. Storiform fibrosis and obliterative phlebitis are diagnostic hallmarks but are sometimes equivocal. Storiform fibrosis is defined as spindle‐shaped cells, inflammatory cells and fine collagen fibers forming a flowing arrangement. Obliterative phlebitis is defined as fibrous venous obliteration with inflammatory cells. Examples of each are provided. The third part describes the differentiation of AIP from pancreatic ductal adenocarcinoma (PDAC), focusing on histological features of acinar‐ductal metaplasia in AIP, which is an important mimicker of PDAC. This guidance will help standardize pathology reports of pancreatic biopsies for diagnosing type 1 AIP.